A histone-mimicking interdomain linker in a multidomain protein modulates multivalent histone binding - Kostrhon, Sebastian; Kontaxis, Georg; Kaufmann, Tanja; Schirghuber, Erika; Kubicek, Stefan; Konrat, Robert; Slade, Dea (The Journal of biological chemistry, 2017)
N-terminal histone tails are subject to many posttranslational modifications that are recognized by and interact with designated reader domains in histone-binding proteins. BROMO domain adjacent to zinc finger 2B (BAZ2B) is a multidomain histone-binding protein that contains two histone reader modules, a plant homeodomain (PHD) and a bromodomain (BRD), linked by a largely disordered linker. Although previous studies have reported specificity of the PHD domain for the unmodified N terminus of histone H3 and of the BRD domain for H3 acetylated at Lys14 (H3K14ac), the exact mode of H3 binding by BAZ2B and its regulation are underexplored. Here, using isothermal titration calorimetry and NMR spectroscopy, we report that acidic residues in the BAZ2B PHD domain are essential for H3 binding and that BAZ2B PHD–BRD establishes a polyvalent interaction with H3K14ac. Furthermore, we provide evidence that the disordered interdomain linker modulates the histone-binding affinity by interacting with the PHD domain. In particular, lysine-rich stretches in the linker, which resemble the positively charged N terminus of histone H3, reduce the binding affinity of the PHD finger toward the histone substrate. Phosphorylation, acetylation, or poly(ADP-ribosyl)ation of the linker residues may therefore act as a cellular mechanism to transiently tune BAZ2B histone-binding affinity. Our findings further support the concept of interdomain linkers serving a dual role in substrate binding by appropriately positioning the adjacent domains and by electrostatically modulating substrate binding. Moreover, inhibition of histone binding by a histone-mimicking interdomain linker represents another example of regulation of protein–protein interactions by intramolecular mimicry.